Incorporating the video communication assessment for error disclosure in residency curricula: a mixed methods study of faculty perceptions - Grossniklaus, Emily; King, Ann M.; D’Addario, Angelo E.; Berg Brigham, Karen; Gallagher, Thomas H.; Musselman, Thea G.; Hester, Kendra; Mazor, Kathleen M.; White, Andrew A. (Frontiers in Health Services, 2025)
IntroductionU.S. resident physicians are required to demonstrate competency in disclosing patient safety events to patients, including harmful errors. The Video-based Communication Assessment (VCA) is a novel tool that provides opportunities to practice and receive feedback on communication skills. VCA practice and feedback are associated with improvements in residents’ error disclosure skills, but no research exists regarding faculty members’ views on implementing the VCA in patient safety curricula. We sought to evaluate faculty members’ views on using the VCA for teaching error disclosure communication in residency, and to identify barriers and facilitators to VCA adoption.MethodsMixed methods study using a validated survey of Acceptability, Appropriateness, and Feasibility (AAF), and thematic content analysis of structured key informant interviews with faculty.Results25 faculty completed both the AAF survey and interview. Overall, the faculty rated the VCA with a mean AAF score of 4.23 (out of 5). Analysis of the interviews identified case quality, relevancy, and fulfillment of a curricular void as attractive aspects of the tool, while feedback delays and content were identified as limitations. A major challenge to implementation included finding curricular time. Faculty anticipated the VCA would be useful for resident remediation and could be used in faculty coaching on error disclosure.ConclusionThe VCA seems to be an acceptable and feasible tool for teaching error disclosure; this finding warrants confirmation and testing in other specialties. Faculty members expected the VCA would be useful for both improving poor performance as well as informing faculty coaching, although these approaches remain untested. To facilitate adoption, faculty recommended protecting curricular time for VCA use and effectively communicating with residents about who will review their personal assessments and how the exercise will support their learning.